Luminescence of Dipole-centers in ZnSe crystals - Alizadeh, M.; Degoda, V.Ya.; Kozhushko, B.V.; Pavlova, N.Yu. (Functional Materials, 2017)
It is proposed a model of recombination luminescence center on which the two opposite mechanisms of recombination, electron and hole recombination, are implemented. Such a center of luminescence is observed in ZnSe crystals and causes the luminescence of a wide band with the maximum at about 1.92 eV (630 nm). It is performed comparison of some characteristics of this center with the characteristics of the center of luminescence which is a point defect and provides the maximum at of 1.27 eV (970 nm). It is shown that the external electric field and temperature have different impacts on the intensity and spectral positions of the maxima of these bands.